PENGARUH LABA BERSIH KOMERSIAL, TAX AVOIDANCE DAN UKURAN PERUSAHAAN TERHADAP TRANSFER PRICING PADA SEKTOR TEKNOLOGI - Susi Mayasari Sihotang (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the effect of commercial profit, tax avoidance, and firm size on transfer pricing practices in technology sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024 47 companies. Transfer pricing is a strategy often used by companies to shift profits to countries with lower tax rates in order to reduce their overall tax burden. The independent variables in this study are commercial profit, tax avoidance, and firm size, while the dependent variable is transfer pricing. This research employs a quantitative approach using multiple linear regression analysis. The sample was selected using purposive sampling, resulting in a total of 6 companies . The data were obtained from annual financial reports published on the official IDX website and other related sources. The results show that, partially, commercial profit, tax avoidance, and firm size have a significant influence on transfer pricing. Simultaneously, all three variables also have a significant effect on transfer pricing. These findings indicate that internal company factors play an important role in influencing managerial decisions related to transfer pricing practices.